THEORETICAL AND PRACTICAL CONSIDERATIONS REGARDING THE COST CALCULATION USING DIRECT COSTING - Cristina Aurora, Bunea-Bontaş (Strategii Manageriale)
The definition of the cost of production as applied to inventories refers to the acquisition and production cost, and its determination involves many considerations. This article emphasizes a comparative approach of the calculation of production cost under direct costing and absorption costing, and examines the impact of using these calculation systems on the financial performance of the companies presented in the income statement.